Analysis of Factors that Influence Brand Switching on Smartphone Products - Mailany, Sofia; Hendra Halim; Syahriyal, Syahriyal (Journal of Finance and Business Digital, 2024)
This study examines the effects of product quality, variety seeking, and advertising on brand switching in smartphone devices among students at Syiah Kuala University's Faculty of Business Economics. Using purposive sampling, 100 questionnaires were distributed, and data were analyzed through multiple linear regression using IBM SPSS Statistics 25. The findings reveal that advertising, product quality, and variety seeking significantly influence brand switching both collectively and individually. These results highlight the critical role of these factors in shaping students' switching behavior. The study provides valuable insights for marketers and smartphone manufacturers to develop effective strategies to enhance customer retention and reduce brand switching among college students. By understanding these factors, businesses can better cater to the preferences and behaviors of their target audience in the competitive smartphone market.